IMPLEMENTATION OF THE 7P MARKETING MIX STRATEGY TO INCREASE THE COMPETITIVENESS OF CULINARY MICRO, SMALL, AND MEDIUM ENTERPRISES (MSMES); CASE STUDY OF KUE LUMPUR MUDA-MUDI - Mubarokah, Umi Chabibah Siti; Hariyanto, Didik (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to analyze the implementation of the 7P marketing mix strategy—Product, Price, Place, Promotion, People, Process, and Physical Evidence—in enhancing the competitiveness of the traditional culinary MSME Kue Lumpur Muda-Mudi. Method: The research employs a descriptive qualitative approach, with data collected through interviews, documentation, and observation to explore how each element of the marketing mix contributes to business performance and customer satisfaction. Results: The findings reveal that the 7P marketing mix strategy has been implemented consistently, particularly in the areas of product quality, competitive pricing, effective promotion, and competent human resources. These aspects have contributed significantly to strengthening customer loyalty and expanding market reach. However, improvements are still needed in process management and physical facilities to enhance customer comfort and satisfaction. Novelty: This study provides a contextual understanding of how the 7P marketing mix can be effectively adapted within traditional culinary MSMEs to maintain competitiveness amid modern market dynamics, thereby offering practical insights for local entrepreneurs seeking sustainable business development.